Perceptions of strength training in dance - Farmer, C.; Brouner, J. (Journal of Dance Medicine & Science, 2021)
The aim of this study was to ascertain current perceptions of strength training (ST) in dance from the viewpoint of the professional dancer, dance teacher, and student dancers across dance genres. A total of 168 responses (149 females, 19 males) to the modified Training Information Survey (TIS) were analyzed for differences in perceptions of ST between dance students, professional dancers, and dance teachers. Some significant differences were found between professionals and teachers (p > 0.05) and between students and teachers (p > 0.001). In all instances, dance teachers were less likely to agree with the following: ST is essential to my overall development as a dancer, women should participate in ST, men should participate in ST, ST should be part of every training program regardless of dance style, ST is beneficial to women, and ST increases bodyweight. It is evident that perceptions of ST still vary across the dance sector, and it is postulated that further education for dancers on the role ST has to play on the development of a dancer would help to break down barriers to participation. From this investigation, it can also be concluded that the perception that dancers have a fear of muscle hypertrophy and a negative impact on aesthetics is no longer widely prevalent, although it still permeates throughout the dance sector.